Antigenic differences between a field isolate and vaccine strains of bovine viral diarrhea virus. - Reddy, J R (1995)
Antigenic diversity among the bovine viral diarrhea virus (BVDV) cytopathic strains 87-2552 (field isolate) and NADL and Singer (prototype strains) was demonstrated with monoclonal antibodies (MAbs) in enzyme-linked immunosorbent, immunofluorescence, virus neutralization, and immunoprecipitation assays. Two MAbs against BVDV strain 87-2552, designated D11 and B7, strongly neutralized this field strain and were specific for the 48-kDa glycoprotein of the virus. These two MAbs have different subisotypes, immunoglobulin G1 for D11 and immunoglobulin G3 for B7. MAbs against BVDV strains 87-2552 and NADL were specific for their respective strains in virus neutralization assays. The results indicated significant antigenic differences between BVDV strain 87-2552 and the NADL and Singer strains.